2020
DOI: 10.3390/pathogens9040302
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of African Swine Fever Virus Exposure to Sus scrofa in Japan Via Pork Products Brought in Air Passengers’ Luggage

Abstract: In recent years, African swine fever (ASF) has become prevalent in many areas, including Asia. The repeated detection of the ASF virus (ASFV) genome in pork products brought in air passenger’s luggage (PPAP) was also reported from Japanese airports. In the present study, the risk of ASFV exposure to susceptible hosts in Japan via three different pathways was assessed. Two quantitative stochastic risk assessment models were built to estimate the annual probability of ASFV exposure to domestic pigs, which could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Since the beginning of the ASF outbreaks in Asia in 2018, several quantitative risk assessments have been conducted of the release of or exposure to ASFV, or both, in a new country or territory through various pathways (Cho et al, 2021;Ito, Bosch, et al, 2020;Sugiura et al, 2020;Taylor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the beginning of the ASF outbreaks in Asia in 2018, several quantitative risk assessments have been conducted of the release of or exposure to ASFV, or both, in a new country or territory through various pathways (Cho et al, 2021;Ito, Bosch, et al, 2020;Sugiura et al, 2020;Taylor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the ASF outbreaks in Asia in 2018, several quantitative risk assessments have been conducted of the release of or exposure to ASFV, or both, in a new country or territory through various pathways (Cho et al., 2021; Ito, Bosch, et al., 2020; Ito, Jurado, et al., 2020; Jurado, Mur, et al., 2019; Sugiura et al., 2020; Taylor et al., 2020). One study from Japan and another from the United States focused on the risk of ASFV release from PPTs carried by international travellers from multiple countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ASF cases have been reported in Asian countries [ 4 ], and previous studies have suggested that the potential risk of ASFV outbreaks and spread might be related to the distributions and habitats of wild boar populations [ 13 , 22 ]. Thus, the staff of wildlife and swine industry need to continuously obtain information on wild boar distribution, properly control the number of wild boars culled, and change the biosecurity level at farms in accordance with wild boar distribution.…”
mentioning
confidence: 99%